Effects of Depth of Propofol and Sevoflurane Anesthesia on Upper Airway Collapsibility, Respiratory Genioglossus Activation, and Breathing in Healthy Volunteers. (September 2016) - Simons, Jeroen C. P.; Pierce, Eric; Diaz-Gil, Daniel; Malviya, Sanjana A.; Meyer, Matthew J.; Timm, Fanny P.; Stokholm, Janne B.; Rosow, Carl E.; Kacmarek, Robert M.; Eikermann, Matthias
Abstract : Background: Volatile anesthetics and propofol impair upper airway stability and possibly respiratory upper airway dilator muscle activity. The magnitudes of these effects have not been compared at equivalent anesthetic doses. We hypothesized that upper airway closing pressure is less negative and genioglossus activity is lower during deep compared with shallow anesthesia. Methods: In a randomized controlled crossover study of 12 volunteers, anesthesia with propofol or sevoflurane was titrated using a pain stimulus to identify the threshold for suppression of motor response to electrical stimulation. Measurements included bispectral index, genioglossus electromyography, ventilation, hypopharyngeal pressure, upper airway closing pressure, and change in end-expiratory lung volume during mask pressure drops. Results: A total of 393 attempted breaths during occlusion maneuvers were analyzed. Upper airway closing pressure was significantly less negative at deep versus shallow anesthesia (−10.8 ± 4.5 vs . −11.3 ± 4.4 cm H2 O, respectively [mean ± SD]) and correlated with the bispectral index ( P < 0.001), indicating a more collapsible airway at deep anesthesia. Respiratory genioglossus activity during airway occlusion was significantly lower at deep compared with light anesthesia (26 ± 21 vs . 35 ± 24% of maximal genioglossus activation, respectively; P < 0.001) and correlated with bispectral index ( P < 0.001). Upper airway closing pressure and genioglossus activity during airway occlusion did not differ between sevoflurane and propofol anesthesia. Conclusions: Propofol and sevoflurane anesthesia increased upper airway collapsibility in a dose-dependent fashion with no difference at equivalent anesthetic concentrations. These effects can in part be explained by a dose-dependent inhibiting effect of anesthetics on respiratory genioglossus activity. Abstract : This randomized controlled crossover study in healthy human volunteers first examined effects of equivalent anesthesia doses of sevoflurane and propofol on pharyngeal airway dilating muscle activity and upper airway collapsibility. Propofol and sevoflurane anesthesia increased upper airway closing pressure in a dose-dependent fashion with no difference at equivalent anesthetic concentrations, possibly mediated by a dose-dependent reduction of genioglossus muscle activation.